Transformasi Ekonomi-Politik Jerman dan Regionalisasi Ekonomi di Asia - Lukman nul Hakim (Jurnal Kajian Wilayah, 2010)
The pressures to transform the Modell Deutschland have been culminated, particularly by the triumph of the ordo-liberal coallitions. Reunification process, European Union regionalism, and economic liberalization waves were the historical momentum in which the ordo-liberal groups gain its legitimacy. Such transformation also brought about in the context of globalizing production system which has massively insisted the German industries to transnationalize and to improve its competitiveness.The expansion of German economy arround the world went hand in hand with the massive regionalization in Asia. The industrial shape since 1980s has been highly attractive for the developed countries to take part in the Asian regionalization. Besides presenting the political economic transformation in Germany, this paper also seeks to examine the significance and the dynamics of its economic networks in Asian regionalization.Kata Kunci: Modell Deutschland, transformasi ekonomi-politik, restrukturasi industrial, jejaring ekonomi, regionalisasi Asia